Physical and mechanical characterization of Mimosa tenuiflora wood from the caatinga for structural applications in construction - Xavier de França Neta Alves, Maria de Lourdes; Cavalcanti Cabral, Kleber; Pinto, Edna; Costa Alves, Rejane; Santos, Rosimeire Cavalcante dos (Maderas. Ciencia y Tecnología, 2025)
The construction industry has been seeking materials that have a lower impact on the built environment. For this reason, wood has become an attractive option due to its natural and renewable properties. In the Northeast region of Brazil, the Caatinga biome stands out for its biodiversity as the only entirely national biome. However, the physical and mechanical properties of local tree species are poorly investigated, limiting potential uses as construction material. Therefore, this study aims to characterize the jurema preta Mimosa tenuiflora (jurema preta) species, native to the Caatinga biome, and indicate potential uses in civil construction. To this end, physical tests were conducted to determine moisture content, basic density, bulk density, dimensional stability, thermal conductivity; mechanical tests for parallel-to-grain compression, parallel and perpendicular shear, parallel and perpendicular tension, Janka hardness parallel and perpendicular, and static bending were performed. The Shapiro-Wilk test and Pearson correlation were used between physical and mechanical properties. The results classify the wood in the D20 strength class, with mechanical properties that meet the standards required for civil construction, covering both light and heavy indoor applications.